Mental Health Burden in Urban Populations: A Cross-Sectional Analysis of Risk Factors and Access to Care - Adhayani Lubis; Ira Aini Dania (Media of Health Research, 2026)
Urban populations face an increasing burden of mental health problems due to complex interactions between socioeconomic, environmental, and psychosocial factors. This study aimed to assess the burden of mental health conditions, identify associated risk factors, and examine access to mental health services in urban settings. A cross-sectional study was conducted among 450 adult respondents selected using multistage sampling. Data were collected through structured questionnaires measuring psychological distress, depression, anxiety, social support, stigma, and healthcare access. Descriptive and inferential statistical analyses, including logistic regression, were performed to identify significant predictors. The results showed that 34.7% of respondents experienced psychological distress, 29.3% reported depression symptoms, and 26.9% experienced anxiety. Low social support, high perceived stigma, low income, and unemployment were significantly associated with higher mental health burden. Only 38.2% of individuals with symptoms accessed mental health services, with cost, stigma, and lack of awareness identified as major barriers. This study highlights that mental health in urban populations is influenced not only by risk exposure but also by limitations in access to care. An integrated approach addressing socioeconomic inequalities, psychosocial support, and healthcare accessibility is essential to reduce the mental health burden and improve service utilization in urban communities.